(untitled) (diségno, 2019)
The Milanese church Santa Maria presso San Satiro documents an experimental integration between perspective and architecture in which the accelerated perspective of the choir simulates a distance comparable to that in the transept. The effectiveness of perspective deception demonstrates the quality of local perspective science and justifies the perspective variables examination, comparing the previous hypotheses in light of a proper survey of choir inserted in the real architecture. The research is based on the interior space three-dimensional reconstruction of the virtual architecture designed by Bramante. Starting from a survey campaign, which integrated direct methodologies with laser scanning, it was identified the privileged point of view, reconstructed through the illusory space digital simulation of Bramante’s architecture. The mounting of 24 point clouds and the subsequent transformation in mesh surfaces allowed us to verify the construction accuracy and to individuate some unknown anomalies hidden by the ornamental apparatus which make difficult to set the point of view in a unambiguous location. The virtual reconstruction highlights a theoretical point of view, different from those already hypothesized and explains the design that identifies the solid perspective of San Satiro as the first model of modern theatrical scenography.